1967
DOI: 10.1677/joe.0.0380061
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Metabolism of a Sertoli Cell Tumour of the Testis of a Dog With Feminization and Alopecia and of the Normal Canine Testis

Abstract: The metabolism of [7\g=a\-3H]pregnenolone and [4-14C]dehydroepiandrosterone (DHA) by a Sertoli cell tumour of the testis from a dog with signs of feminization has been studied in vitro and compared with the metabolism of the normal canine testis.The tumour formed oestrone and oestradiol-17\g=b\ from DHA thus providing direct evidence for the synthesis of oestrogen by this type of neoplasm.Relative or complete inactivity of several enzyme systems involved in the synthesis of testosterone was found in the tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1971
1971
1979
1979

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 8 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…5-Androstene-3^, 17^-diol and 5a-androstane-3j?, 17^-diol show a tendency to cocrystallize but can be distinguished by further crystallization of their oxidation products. During oxidation with chromic acid (Bush 1961) [7a-^H]5a-androstane-3jS, 17^-diol is converted to [7a-^H]5a-androstanedione while [7a-^H]5-androstene-3j9, i7j?-diol is converted to 4-androstene-3,6, 17-trione with loss of 7a-^H (Pierrepoint et al, 1967).…”
Section: Isolation and Determination Of Steroidsmentioning
confidence: 99%
“…5-Androstene-3^, 17^-diol and 5a-androstane-3j?, 17^-diol show a tendency to cocrystallize but can be distinguished by further crystallization of their oxidation products. During oxidation with chromic acid (Bush 1961) [7a-^H]5a-androstane-3jS, 17^-diol is converted to [7a-^H]5a-androstanedione while [7a-^H]5-androstene-3j9, i7j?-diol is converted to 4-androstene-3,6, 17-trione with loss of 7a-^H (Pierrepoint et al, 1967).…”
Section: Isolation and Determination Of Steroidsmentioning
confidence: 99%
“…Indeed in some Sertoli cell tumours an oestrogenic substance has been detected by Huggins 8c Moulder (1945), while Pierrepoint et al (1967) have demonstrated that Sertoli cell tumour tissue of feminized dogs can convert dehydroepiandrosterone and testosterone to oestrone and oestradiol-17/?. Indeed in some Sertoli cell tumours an oestrogenic substance has been detected by Huggins 8c Moulder (1945), while Pierrepoint et al (1967) have demonstrated that Sertoli cell tumour tissue of feminized dogs can convert dehydroepiandrosterone and testosterone to oestrone and oestradiol-17/?.…”
mentioning
confidence: 94%
“…The incidence of testicular tumours is higher in the dog than in any other species, almost all are derived from Sertoli-, interstitial-, or spermatogonial cells; teratomas have never been recorded (Dow 1962). Sertoli cell tumour tissue seems capable of converting under in vitro conditions dehydroepiandrosterone and testosterone to oestrone and oestradiol-17/3 (Pierrepoint et al 1967). The presence of an oestrogenic substance in some of these tumours (Huggins 8c Moulder 1945) and in the urine of affected dogs (Brodey 8c Martin 1958;Siegel et al 1967) has been demonstrated.…”
mentioning
confidence: 99%